Анализа корелације нивоа сира СИР2Л4, Ц1КТНФ5 и ЦБП-35 у серуму са прогнозом пацијената са дијабетичком ретинопатијом: Нивои серума SIR2L4, C1QTNF5 и CBP-35 код пацијената са дијабетичком ретинопатијом - Cheng, Wenming; Lu, Hua; Song, Ting; Liu, Wei (Journal of Medical Biochemistry, 2025)
Objective: To explore the relationships between serum Silent Mating Type Information Regulation 2 Homolog 4 (SIR2L4), C1q and tumor necrosis factor related protein 5 (C1QTNF5), Carbohydrate-binding protein 35 (CBP-35) and glycolipid metabolism and prognosis in patients with diabetic retinopathy (DR).Methods: The DR group was selected from among 230 hospitalised DR patients admitted between January 2023 and January 2024, including 122 non-proliferative DR patients (Non-proliferative DR group) and 108 proliferative DR patients (Proliferative DR group). Additionally, 100 subjects who underwent health check-ups in the hospital during the same period were selected as the control group. Indicators of SIR2L4, C1QTNF5, CBP-35, blood glucose [Fasting plasma glucose (FPG)], and the levels of blood lipids in the DR group and the control group were measured and compared. Triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and total cholesterol (TC) were among them. Moreover, the correlations between serum SIR2L4, C1QTNF5, and CBP-35 levels and blood glucose and lipid indicators in DR patients were analysed. The DR patients were monitored and followed up with for six months after treatment. Depending on their level of visual impairment, the patients were split into groups with excellent and poor prognoses. The levels of serum SIR2L4, C1QTNF5 and CBP-35 in the two groups were compared. Multivariate logistic regression was used to analyse the risk factors for poor prognosis in DR patients. A receiver operating characteristic (ROC) curve was used to analyse the predictive value of single or combined detection of SIR2L4, C1QTNF5, and CBP-35 for poor prognosis in patients with DR.Results: Pearson correlation analysis revealed that the levels of SIR2L4, C1QTNF5, and CBP-35 in DR patients were positively correlated with FPG, TG, TC, and LDL-C (P
Keywords: Дијабетичка ретинопатија; Тихи фактор модерације информација 4; C1q и протеин повезан са фактором некрозе тумора 5; ЦБП-35; Метаболизам гликолипида